Does speculative news hurt productivity? Evidence from takeover rumors - Christian Andres; Dmitry Bazhutov; Douglas J. Cumming; Peter Limbach (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
Speculative news on corporate takeovers may hurt productivity because uncertainty and threat of job loss cause anxiety, distraction, and reduced collaboration and morale among employees and managers. Using a panel of OECD-headquartered firms, we show that firm productivity temporarily declines upon announcements of speculative takeover rumors that do not materialize. This productivity dip is more pronounced for targets and for firms in countries with weaker employee rights and less long-term orientation. Abnormal stock returns mirror these results. The evidence fosters our understanding of potential real effects of speculative financial news and the costs of takeover threats.
urn:nbn:de:hebis:30:3-689951
Keywords: D24; G00; G34; J24; 330; Distraction; Employee commitment; Employee rights; Fear of job loss; Productivity; Shareholder wealth; Takeover speculation; Distraction